Implementation of Storytelling Abilities of Early Childhood Teachers in Early Childhood Education Cluster IV, Kacang Panjang, Cempaka Putih, Central Jakarta - Sari, Euis Agung; Puridawaty, Brigita (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study describes the implementation of storytelling skills of Early Childhood Education teachers on Cluster 4 Early Childhood Education in Kacang Panjang, Cempaka Putih District, Central Jakarta. Storytelling is an important learning method in early childhood education to develop literacy, imagination, and children's social-emotional skills. This study used a survey method in a descriptive study involving 40 Early Childhood Education teachers from 8 educational institutions in the area. Data were obtained through a Yes-No choice test consisting of 22 statement items. The results of data analysis and discussion showed that the implementation of storytelling skills of Early Childhood Education teachers on Cluster 4 Early Childhood Education in Kacang Panjang, Cempaka Putih, Central Jakarta was in the "Low" category of 47.5% (19 teachers), "Medium" of 45% (18 teachers), and "High" of 7.5% (3 teachers). Based on the average value, which is 8.1%, the level of implementation of storytelling skills of EARLY CHILDHOOD EDUCATION teachers on Cluster 4 Early Childhood Education in Kacang Panjang, Cempaka Putih, Central Jakarta is in the "MEDIUM" category.